Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian dan Program Pascasarjana Universitas Sriwijaya - ANDY MULYANA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
The objective of the research is to find out the position of fresh fruit bunch (FFB) price of oil palmdetermined by regional government in a range of its price predicted by bilateral monopoly marketapproach, meaning that whether it have protected plasma farmers and reaching a price that reflectedbalance bargaining positions, or it tended to come close to a monopsonist price or to monopolist price.Three nucleus estate smallholders (NES) types was selected as samples to be examined their conditionand data (1998-2002) in this research, which were NES-Transmigration managed by private andpublic firms, and NES of small scale credit type. Single equations analyses of econometric modelwere used to estimate FFB price and volume in constructing demand and supply curves of thecommodity. The results show that the determined FFB price is proven to have protected farmers frommonopsonist price application without that intervention. However, the its level in bilateral monopolymarket perspective, in which KUD representing farmers as a monopolist, still closed to monopsonistprice. This also reflects stronger bargaining power of the nucleus firm than the plasma farmers, andthe status of FFB price as a derivation of world CPO price. More strong commitment and seriousattempt are needed from both sides to increase partnerships works in order to obtain fair FFB price inthe future.